EGMR 16213/90 vom 22. Februar 1994 , CASE OF BURGHARTZ v. SWITZERLAND - Hudoc Ch (1994)
Preliminary objection rejected (victim);Preliminary objection rejected (non-exhaustion);Violation of Art. 14+8;Not necessary to examine Art. 8;Costs and expenses partial award - domestic proceedings;Costs and expenses partial award - Convention proceedings; Violation: 14+8;14;8